Mechanical ventilation in critically-ill pregnant women: a case series. Issue 4 (November 2015) - Lapinsky, S.E.; Rojas-Suarez, J.A.; Crozier, T.M.; Vasquez, D.N.; Barrett, N.; Austin, K.; Plotnikow, G.A.; Orellano, K.; Bourjeily, G.
Highlights We reviewed 29 pregnant women with respiratory failure who required mechanical ventilation. Ventilatory approach was similar to non-pregnant patients. Mild hypercapnia was common and may be tolerated in pregnancy. Delivery of the baby improved respiratory function in some but not all patients.